KONTRIBUSI ROYALTI PT NEWMONT NUSA TENGGARA TERHADAP PENDAPATAN DAERAH KABUPATEN SUMBAWA BARAT TAHUN 2006-2012 - Purwadinata, Subhan (Jurnal Ilmu Ekonomi dan Pembangunan, 2016)
Contributions Royalty PT Newmont Nusa Tenggara to the regional income West Sumbawa Regency Year 2006-2012. The purpose of this study was to investigate the contribution of royalty PT NNT to the regional income West Sumbawa. In this study, secondary data on the realization of royalty PT NNT and regional income data for the year 2006-2012. The data comes from the offices of the financial revenues of West Sumbawa. This study uses a quantitative approach simple statistics. The results of this study indicate that the variable royalty contribute positively to regional income West Sumbawa regency in 2006-2012. This is indicated by the value of the contributions made by the variable royalty PT NNT to the regional income Sumbawa district from 2006 amounted to 21.70%, in 2007 13.69 decreased in 2008 decreased 1.05 percent from the year 2008 amounted to 12.64 percent , Then in 2009 the contribution of royalty PT NNT rose 13.78 percent and in 2010, 2011 and 2012 contributions amounting to 11.56 percent and 08.16 percent. The conclusion from this study is that the variable royalty PT Newmont Nusa Tenggara has contributed greatly to the increase of regional income West Sumbawa regency during 2006-2012.